2021
DOI: 10.1016/j.bbih.2021.100199
|View full text |Cite|
|
Sign up to set email alerts
|

The role of dopamine receptors in lymphocytes and their changes in schizophrenia

Abstract: Dopamine and its 5 receptors, which are grouped into two families (D1-like and D2-like), modulate functions at a systemic level in both the central nervous system and periphery. The central nervous system and the immune system are the main adaptive systems, which participate in a continuous and functional crosstalk to guarantee homeostasis. On binding to its 5 dopamine receptors, dopamine acts as a co-regulator of the immune system, contributing to the interaction of the central nervous system and inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 92 publications
(193 reference statements)
0
13
0
Order By: Relevance
“…Experimental evidence, such as the association between the level of activation of the inflammatory response and schizophrenia, seems to suggest a role for stress in this condition [71][72][73][74]. Moreover, differences in this inflammatory response have also been noticed between schizophrenia and treatment-resistant schizophrenia [73,[75][76][77][78].…”
Section: Interpretation Of the Functional Analysismentioning
confidence: 99%
“…Experimental evidence, such as the association between the level of activation of the inflammatory response and schizophrenia, seems to suggest a role for stress in this condition [71][72][73][74]. Moreover, differences in this inflammatory response have also been noticed between schizophrenia and treatment-resistant schizophrenia [73,[75][76][77][78].…”
Section: Interpretation Of the Functional Analysismentioning
confidence: 99%
“…However, as peripheral immune cells are easily accessible in blood samples, these cells could potentially be used to monitor the status of homologous brain dopamine receptors ( Buttarelli et al, 2011 ; Tomasik et al, 2016 ). They may also be useful tools with which to monitor changes in dopamine receptor expression with respect to the efficacy of therapeutic interventions ( Buttarelli et al, 2011 ; Penedo et al, 2021 ). Using these types of data could enable a more nuanced usage of novel and repurposed anti-inflammatory and/or dopaminergic drugs as adjuvant therapies for schizophrenia and could provide novel targets and substantial improvements in the treatment and symptomatology involved in this disorder.…”
Section: Regional and Disease-specific Effects Of Dopaminementioning
confidence: 99%
“…In 2017, Mlcochova et al showed that the absence of restriction by sterile alpha motif and histidine/aspartic acid domain-containing protein 1 (SAMDH1) restriction factor (RF) sterile alpha motif (SAM) was because it was phosphorylated by cyclin kinase 1 (CDK1), and it itself was induced in microglial cells cycling between G 0 to G 1 states [ 61 ] ( Table 1 ). Taken together, these clues indicate that microglia are infected by HIV-1 both in vitro and in vivo [ 20 ].…”
Section: The Entry Of Hiv-1 Into Microglial Cells and Their Susceptibility To The Virus Relevant Studies About The Mechanism Of Infectionmentioning
confidence: 99%
“…Macrophages or microglia can provoke the release of pr-inflammatory cytokines, including tumor necrosis factor α (TNFα), interferon α (IFNα), interleukin-6 (IL6), interleukin-8 (IL8), and interleukin-1β (IL1β) [ 6 , 8 , 13 ] ( Figure 1 ), as well as chemokines (C-C motif chemokine ligand 2 (CCL2) and C-C motif chemokine ligand 5 (CCL5), macrophage inflammatory protein 1β (MIP)-1β) [ 17 ]. These clues indicate the existence of cellular reservoirs in the CNS established within 3 to 5 days of HIV-1 infection [ 8 ], comprising three different types of long-lived infected cells [ 18 ]: astrocytes, monocyte lineage cells [ 19 ], and microglial cells [ 20 ].…”
Section: Introductionmentioning
confidence: 99%